Konstruksi Pengetahuan Ibu Muda Dalam Pola Asuh Anak Di Desa Sindangsari - Pipi Amelia; Deny Soetrisnaadjisendjaja; Haryono . (Universitas Lambung Mangkurat, 2024)
Parent are role models for children, in every process they can determine the child’s character. Involvement in parenting and adjustment to children is where parents play a role. This research aims to determine the construction of young mother’s knowledge in parenting patterns in Sindangsari Village. The method used is qualitative with a case study type of research. The results of the research explain that the contructions of young mother’s knowledge in parenting patterns in Sindangsari Village occurs through a social contructions process, namely externalization, objectavation, and internalization. It was concluded that the parenting patterns applied by young mothers were driven by belief factors. Where, young mother learn from the past, namely the treatment they receive or learn from the surrounding situations. The types of parenting chosen by young mothers in Sindangsari Village are democratic parenting and permissive parenting.